Resenha do livro Forjando a democracia – a história da esquerda na Europa, 1850-2000 de Geoff Eley - Aggio, Alberto (Anos 90, 2006)
Resenha do livro Forjando a democracia – a história da esquerda na Europa, 1850-2000 de Geoff Eley.